KEBIJAKAN PENEGAKAN HUKUM DALAM PEMBERANTASAN NARKOTIKA PENYALAGUNAAN DALAM TAHANAN OLEH BADAN NARKOTIKA NASIONAL - Sunggara, Muhammad Adystia (Solusi, 2020)
Narcotics crime in Indonesia is increasing. Law enforcement continues to push but these crimes remain higher. One reason is easy access to narcotics in the market. This study discusses whether law enforcement policies in eradicating narcotics among inmates have been effective and what obstacles are faced by BNN in carrying out enforcement of narcotics eradication law among inmates. The study was conducted using empirical juridical methods with descriptive analytical research specifications. Resource persons in this study are BNN Central Java Province and Narcotics Prison. The analysis of this research uses descriptive qualitative and content analysis using legal interpretation, legal principles and legal theories. This research uses the Research and Development analysis method. The handling of drug use by the National Narcotics Agency in prison is still not optimal because there are obstacles in the form of a lack of prison staff to monitor the target people.